Floods and financial stability: Scenario-based evidence from below sea level - Francesco G. Caloia; Kees C. H. van Ginkel; David-Jan Jansen (Tinbergen Institute, 2023)
We study whether floods can affect financial stability through a credit risk channel. Our focus is on the Netherlands, a country situated partly below sea level, where insurance policies exclude property damages caused by some types of floods. Using geocoded data for close to EUR 650 billion in real estate exposures, we consider possible implications of such floods for bank capital. For a set of 38 adverse scenarios, we estimate that flood-related property damages lead to capital declines that mostly range between 30 and 50 basis points. We highlight how starting-point loan-to-value ratios are one important driver of capital impacts. Our estimates focus on property damages as the main transmission channel and are also subject to a number of assumptions. If climate change continues, more frequent floods or flood-related macrofinancial disruptions may have stronger implications for financial stability than our estimates so far indicate.
Keywords: G21; Q54; R30; 330; floods; financial stability; real estate; credit risk; climate change